Microglia Polarization: A Novel Target of Exosome for Stroke Treatment - Wan, Teng; Huang, Yunling; Gao, Xiaoyu; Wu, Wanpeng; Guo, Weiming (Frontiers in Cell and Developmental Biology, 2022)
The vast majority of cells in the human body are capable of secreting exosomes. Exosomes have become an important vehicle for signaling between cells. Exosomes secreted by different cells have some of the structural and functional properties of that cell and thus have different regulatory functions. A large number of recent experimental studies have shown that exosomes from different sources have different regulatory effects on stroke, and the mechanisms still need to be elucidated. Microglia are core members of central intrinsic immune regulatory cells, which play an important regulatory role in the pathogenesis and progression of stroke. M1 microglia cause neuroinflammation and induce neurotoxic effects, while M2 microglia inhibit neuroinflammation and promote neurogenesis, thus exerting a series of neuroprotective effects. It was found that there is a close link between exosomes and microglia polarization, and that exosome inclusions such as microRNAs play a regulatory role in the M1/M2 polarization of microglia. This research reviews the role of exosomes in the regulation of microglia polarization and reveals their potential value in stroke treatment.